Costs on Consumers in E-Commerce Transactions - Lim, Julian Chu Heing (2007)
This study analyses various transaction costs that are commonly incurred in e-commerce transactions. Multiple approaches were undertaken in this study to understand Malaysians' perception of transaction costs, which are the significance of each transaction costs to Malaysians, the trade-offs they are willing to make, the ranking of transaction costs and the relationships among various transaction costs. The transaction costs analysed here are market cost, search cost, information cost, negotiation cost, monitoring cost, enforcement cost, advertising cost and trust cost, which comprises of branding cost, security cost and privacy cost. These transaction costs were categorised into transaction-specific costs and generic costs and placed in a conceptual framework. A survey was conducted to obtain Malaysian consumers’ perspective on the 10 transaction costs. From this study, it was found that consumers rank branding cost to be the most significant cost to them. This is followed by privacy and security cost. On the flip side, advertising cost was found to be the least significant. The information gathered from this study will assist web owners and designers in developing, enhancing and identifying opportunities in online services.